2017
DOI: 10.3346/jkms.2017.32.5.713
|View full text |Cite
|
Sign up to set email alerts
|

Predatory Publishing Is a Threat to Non-Mainstream Science

Abstract: This article highlights the issue of wasteful publishing practices that primarily affect non-mainstream science countries and rapidly growing academic disciplines. Numerous start-up open access publishers with soft or nonexistent quality checks and huge commercial interests have created a global crisis in the publishing market. Their publishing practices have been thoroughly examined, leading to the blacklisting of many journals by Jeffrey Beall. However, it appears that some subscription journals are also fal… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
21
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 30 publications
(21 citation statements)
references
References 35 publications
0
21
0
Order By: Relevance
“…et al, 2015; Seethapathy et al, 2016;Balehegn, 2017;Gasparyan et al, 2017). It thus seems that many aquaculture researchers from these regions are spending a fair proportion of their limited financial resources on publishing in likely predatory OA journals, when such resources can be used in more effective ways (e.g., increasing research infrastructure, publishing in high quality open access journals, hiring staff).…”
Section: Predatory Oa Publishing As a Source Of Misinformation In Aqumentioning
confidence: 99%
See 1 more Smart Citation
“…et al, 2015; Seethapathy et al, 2016;Balehegn, 2017;Gasparyan et al, 2017). It thus seems that many aquaculture researchers from these regions are spending a fair proportion of their limited financial resources on publishing in likely predatory OA journals, when such resources can be used in more effective ways (e.g., increasing research infrastructure, publishing in high quality open access journals, hiring staff).…”
Section: Predatory Oa Publishing As a Source Of Misinformation In Aqumentioning
confidence: 99%
“…Furthermore, predatory OA journals can provide an outlet for the publication of research from nations that are often excluded (intentionally or not) from Western publishing outlets. Indeed it is reported that the majority of authors publishing in these journals are researchers in developing nations who could better use their funds to stimulate research activities or publish in nonpredatory open access journals (Shen and Björk, 2015;Xia et al, 2015;Seethapathy et al, 2016;Balehegn, 2017;Gasparyan et al, 2017). Consequently, predatory publishing practices threaten the institution of science, undermine legitimate open access journals, and hinder progression of the utilitarian concept of open science on a global scale.…”
Section: Introductionmentioning
confidence: 99%
“…The implications of these metrics are often framed in such a manner as to appear to guarantee a wave of poor quality articles threatening to engulf the very fabric of research and science (Beall, 2016(Beall, , 2017Gasparyan et al, 2017;Johal et al, 2017;Revés et al, 2018;Shen & Björk, 2015). Few commentators have voiced a contrary opinion (see Bell, 2017 for an example of an author that is less damning of predatory publishers).…”
mentioning
confidence: 99%
“…1 ) In 2008, he began creating his own list of predatory publishers, which has been known as Beall's List. 2 ) Since then, predatory publishers have increased, especially in countries such as India, where there is a greater need, ability and personnel able to publish quickly for academics who wish to earn tenure or promotion.…”
mentioning
confidence: 99%
“…2) 3) 4) 1) Assistant Professor, Department of International Medical Communications, Tokyo Medical University 2) Emeritus Professor, Tokyo Medical University 3) Council Member, COPE 4) Adjunct Professor, Seoul National University Bundang Hospital Today there is tremendous pressure to publish scientific articles. This is a particular problem for non-native speakers of English whose research may be excellent but who have difficulty in expressing themselves in a style favored by the reviewers of their target journal.…”
mentioning
confidence: 99%